Study of operational losses of block raw materials - S.S.; O.M.; G.V.; A.H.; O.A. (Технічна інженерія, 2023)
The work investigates operational losses depending on the method of mining and substantiates the methods of control and management of the quality of the natural stone massif. As a result of the conducted research, based on the application of modern qualimetric and information-computer technologies, a connection between mining technologies common in practice and the quality of the final marketable product was established, a methodology for evaluating quality indicators for block raw materials was developed using modern information-computer technologies. The study of operational losses when using a wire sawing unit and diamond ropes of various manufacturers, operational losses when using blasting methods of natural stone extraction and operational losses when using rock wedge technologies was carried out. On the basis of these studies, the paper has developed recommendations regarding the optimal size of blocks and improving the methods of stone preparation for extraction, the technology of separating monoliths from the massif and dividing them into conditioned blocks with a high blockability coefficient and improving their quality and reducing losses of natural stone during extraction.